Three cheers for dispositions: a dispositional approach to acting for a normative reason - Mantel, Susanne (Erkenntnis, 2017)
Agents sometimes act for normative reasons—for reasons that objectively favor their actions. Jill, for instance, calls a doctor for the normative reason that Kate is injured. In this article I explore a dispositional approach to acting for a normative reason. I argue for the need of epistemic, motivational, and executional dispositional elements of a theory of acting for a normative reason. Dispositions play a mediating role between, on the one hand, the normative reason and its normative force, and the action on the other hand. Thereby, they help to deal with problem cases such as cases of deviant causal chains and improper instrumental motivation.
Online veröffentlicht: 26. Juli 2016
Gesehen am 23.12.2025